The role of agricultural policies in rural development/ comparative study between Iran and Japan - Zohreh Najafi Asl, Mehdi Taleb,Ali Shakoori (Kufa Journal for Agricultural Sciences)
Japan’s area is a quarter of Iran’s and it has twice the population. The country has used agricultural and rural economic policies based on productive and patriotic culture and has prioritized national interest over individual interest to be able to produce most of its required agricultural products itself. Japan has used success in agriculture as a theme for its industrialization. On the other hand, Iran, despite its opulent natural resources, has been unsuccessful to do so. The country has relied on oil export income and has embarked upon extreme imports of agricultural products. It is not self-sufficient in food products and is dependent onindustrial sector. The present research has studied agricultural and rural policies in Iran and Japan and has considered the cultural roots of these decisions.